The Baltic States in new economy: FDI, technology flows and innovativeness - Małgorzata Runiewicz (Transformation, Integration and Globalization Economic Research (TIGER), 2004)
The aim of this paper is to evaluate the role of FDI in technology transfer and innovativeness of the Baltic States economies. The latter factors have also become main prerequisites of the Baltic States entrance into the era of 'new economy'. The author exploited the data from various sources, e.g. aggregate indicators from official data, national innovation sources, international reports and own calculations based on the companies survey. The paper provides the broad analysis of the role of technology-transfer and investments into R&D in domestic and foreign owned companies based on the empirical evidence as well as the contribution of FDI to development of ITC sector in Baltic States. The future place of the Baltic States in the 'new economy' will largely depend on their innovative capacity. The paper presents the main indicators of their innovation potential and elements of national innovation systems. A short summary and some general implications towards the future FDI flows into Baltic economies conclude the paper.
Keywords: 330; Auslandsinvestition; Technologietransfer; Innovation; Baltische Staaten; New Economy